Strategi Komunikasi Dakwah Jamaah Tabligh Masjid Jami’ Al Burhan Terhadap Anak Punk di Palembang - Mika, Laswan; Syarifudin, Achmad; Hidayat (Indonesian Journal Publisher, 2024)
This research is entitled